New Horizons for Ecotourism in Sikkim: An Integrated MCDA Approach - Rai, Deepa; Krishnaiah, Y V; Panja , Kausik; Chakma, Atoshi; Mallick, Manika; Das, Debasis; Hati, Moumita (International Journal of Ecology and Environmental Sciences, 2024)
The present paper is an attempt to explore the new horizon of potential ecotourism in Sikkim by analysing thirteen key factors, including elevation, NDVI, protected areas, slope, rainfall, temperature, proximity to cultural heritage sites, roads, urban areas, lakes, rivers, waterfalls, and international boundaries with using the Analytical Hierarchy Process (AHP) and Decision-Making Trial and Evaluation Laboratory (DEMATEL) techniques. Further, it assigns weight to each factor to determine their importance in assessing and mapping the potential of ecotourism using Geographic Information System (GIS) technology to identify the best suited for ecotourism. The potential ecotourism map is reclassified into four categories that are high, moderate, low, and unsuitable. The outcome indicates that 62% of the state’s total geographical area is categorized as highly to moderately suitable (4390 km2) for the development of ecotourism largely distributed across the southern and central parts of the state, whereas 33% under low and remains at 5% of the total geographical area is unsuitable for practicing ecotourism. In addition, the investigator has identified 14 new horizons for developing potential ecotourism in Sikkim.